Properties of bio-based controlled low strength materials. (30th November 2020) - Ahadzadeh Ghanad, D.; Soliman, A.; Godbout, S.; Palacios, J.
Highlights: Bio-based CLSM for farm applications is a feasible method for reusing such waste. Dry/wet cycles adversely affected the volume stability of bio-based CLSM. Reduction in the compressive strength was within the acceptable limit for CLSM. Bio-Based CLSM mixtures are easily excavatable with removability modulus less than 1. Abstract: This study investigates the feasibility of enhancing construction materials sustainability using bio-based by-products as a partial replacement for natural sand. Controlled low strength material (CLSM) was selected as a practical application, thanks to its low strength requirements. The fine black spruce residual was added to different strength levels CLSM mixtures at rates 0%, 5%, 10%, and 20% as a partial replacement of natural sand. Fresh and hardened properties, including flowability, bleeding, density, compressive and tensile strengths, were evaluated. CLSM mixtures incorporating fine black spruce residuals were exposed to sulfate environment to examine their durability. The experimental results demonstrate that adding spruce-residuals had reduced the compressive strength; however, this reduction was within the acceptable limit. Moreover, results indicated that mixtures with high cement content could incorporate >20% spruce-residuals while maintaining adequate performance. The fine spruce-residuals have some filling effect and can reduce the pores leading to lower absorption rates. Dry/wet cycles will adversely affect the volume stability of CLSM, forming wide cracks that, in turn, accelerate degradation. Producing CLSM for farm applications is a feasible method for reusing such waste.